Human α3β4 Neuronal Nicotinic Receptors Show Different Stoichiometry if They Are Expressed in Xenopus Oocytes or Mammalian HEK293 Cells - Krashia, Paraskevi (Public Library of Science, 2010)
BACKGROUND: The neuronal nicotinic receptors that mediate excitatory transmission in autonomic ganglia are thought to be formed mainly by the α3 and β4 subunits. Expressing this composition in oocytes fails to reproduce the properties of ganglionic receptors, which may also incorporate the α5 and/or β2 subunits. We compared the properties of human α3β4 neuronal nicotinic receptors expressed in Human embryonic kidney cells (HEK293) and in Xenopus oocytes, to examine the effect of the expression system and α∶β subunit ratio. METHODOLOGY/PRINCIPAL FINDINGS: Two distinct channel forms were observed: these are likely to correspond to different stoichiometries of the receptor, with two or three copies of the α subunit, as reported for α4β2 channels. This interpretation is supported by the pattern of change in acetylcholine (ACh) sensitivity observed when a hydrophilic Leu to Thr mutation was inserted in position 9′ of the second transmembrane domain, as the effect of mutating the more abundant subunit is greater. Unlike α4β2 channels, for α3β4 receptors the putative two-α form is the predominant one in oocytes (at 1∶1 α∶β cRNA ratio). This two-α form has a slightly higher ACh sensitivity (about 3-fold in oocytes), and displays potentiation by zinc. The putative three-α form is the predominant one in HEK cells transfected with a 1∶1 α∶β DNA ratio or in oocytes at 9∶1 α∶β RNA ratio, and is more sensitive to dimethylphenylpiperazinium (DMPP) than to ACh. In outside-out single-channel recordings, the putative two-α form opened to distinctive long bursts (100 ms or more) with low conductance (26 pS), whereas the three-α form gave rise to short bursts (14 ms) of high conductance (39 pS). CONCLUSIONS/SIGNIFICANCE: Like other neuronal nicotinic receptors, the α3β4 receptor can exist in two different stoichiometries, depending on whether it is expressed in oocytes or in mammalian cell lines and on the ratio of subunits transfected.